Studies on uterine microbial isolates from endometric crossbred cows with reference to antibiogram, treatment and conception rate - KUSUM, K; ROY, G P; KUNJ, V; ASTHANA, R K; AKHTAR, M H (The Indian Journal of Animal Reproduction, 2023)
Abnormal parturition commonly leads to endometritis in crossbred cows. The husbandry and sanitationpractices commonly used in tQe management of dairy crossbred cows during parturition are inadequate andexpose the items to a broad range of bacterial agents resulting in increased incidence ofendometritis in crossbredcows. The study was conducted to know the antibiogram pattern of endometric cows in field condition.
Keywords: Microbial isolates; Endometritis; Crossbred cows; Conception rate